Consultations as a tool. The Finnmark Act : an example to follow? - Broderstad, Else Grete (University of Tromsø, 2006)
Presentation at the 7th annual Forum for Development Cooperation with Indigenous Peoples, which commenced the 5th-6th of October 2006. The Centre for Sámi Studies hosted the conference at the University of Tromsø, Norway. Full conference report is available in Munin at http://hdl.handle.net/10037/2996